Phase I, multicentre, dose‐escalation trial of monotherapy with milatuzumab (humanized anti‐CD74 monoclonal antibody) in relapsed or refractory multiple myeloma. (25th September 2013) - Kaufman, Jonathan L.; Niesvizky, Ruben; Stadtmauer, Edward A.; Chanan‐Khan, Asher; Siegel, David; Horne, Heather; Wegener, William A.; Goldenberg, David M.
Summary: CD74, expressed in multiple myeloma (MM), was evaluated as a target for immunotherapy with milatuzumab (a humanized anti‐CD74 antibody). In a multicentre dose escalation study, 25 patients with advanced MM received milatuzumab doses of 1·5 ( N = 8), 4·0 ( N = 9), 8·0 ( N = 4) or 16·0 mg/kg ( N = 4) administered twice weekly x 4. They had a median of 5 prior treatments (17 post ≥1 stem cell transplantation) and were refractory ( N = 7) or relapsed ( N = 18) with generally short‐lived responses to last treatment (median 4·0 months). After increasing prophylactic medications and slowing administration, infusions were well tolerated (National Cancer Institute‐Common Terminology Criteria v3 toxicity Grades 1–2) with no dose‐limiting toxicity at higher doses. Only one patient developed borderline positive human anti‐milatuzumab antibody titres of uncertain clinical significance. Although milatuzumab was rapidly cleared from circulation with little serum accumulation and low trough levels, B‐cell levels were moderately decreased with treatment (median decrease, 34%). There were no objective responses by European Group for Blood and Marrow Transplantation criteria, but 5 of 19 patients (26%) who completed treatment in this heavily pretreated and generally refractory group had stable disease for ≥3 months post‐treatment (one continuing for 17 months). Disease stabilization and evidence of pharmacodynamic activity support further development for use in combination with other agents or as a drug conjugate. (Clinicaltrials.gov identifier: NCT00421525)